Farnesol induces cell detachment from established S. epidermidis biofilms - Cerca, Nuno (2013)
Antibiotic resistance is a serious problem in Staphylococcus epidermidis infections as many clinical isolates of this organism are resistant to up to eight different antibiotics. The increased resistance to conventional antibiotic therapy has lead to the search for new antimicrobial therapeutic agents. Farnesol, an essential oil found in many plants, has been shown to be active against S. epidermidis. Using a type control strain we recently described that although farnesol was not efficient at killing biofilm bacteria, a strong reduction on biofilm biomass was detected, and we hypothesize that farnesol could, somehow, induce biofilm detachment. In this report, to test our hypothesis we used 36 representative clinical strains of S. epidermidis from different geographic locations and characterized them in terms of genetic variability by multilocus sequence typing and staphylococcal chromosome cassette mec. Strains were tested for biofilm formation, and the presence of ica, bhp and aap genes was determined. Stronger biofilms had always the presence of ica operon but often co-harbored bhp and aap genes. Farnesol was then used in biofilm-forming strains, and biofilm detachment was detected in half of the strains tested. Furthermore, we also showed that farnesol inability to kill biofilm bacteria was not the result of the biofilm structure but was related to high cell density. Our results demonstrate, for the first time, that the biomass reduction previously found by us, and many other groups, is the result not of cell killing but instead is the result of biofilm detachment.